Meriam Puntung: Legenda, Nilai Islam, dan Identitas Budaya Melayu Deli di Medan - Sri Windari; Erfida Mahlizah; Oktatia Ramadhani Afhar; Revi Fadillah; Sahlan Al-Muqaharram Sipahutar; Wilda Nur Hafizah (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2026)
This study is driven by the emerging threats of desacralization and cultural commodification facing the Meriam Puntung Site at the Maimun Palace Complex, Medan, due to mass urban tourism. Additionally, a theoretical dichotomy persists, separating colonial historical facts from the local myth of the Hikayat Putri Hijau. This study aims to analyze the historical-mythological dialectics of Meriam Puntung and map out how the Malay Deli community executes cultural Islamization regarding this narrative. Utilizing a qualitative descriptive method with hermeneutic and usul al-fiqh approaches, we gathered primary data through direct field observations at Maimun Palace and in-depth interviews with the site custodian. The findings reveal that the local community successfully engaged in cultural adaptation, shifting the narrative status from ‘urf fāsid (corrupted custom) to ‘urf ṣaḥīḥ (valid custom). The magical-mystical elements of the cannon fragments are theologically transformed into symbols of nusrullah (divine intervention), the spirit of jihad fi sabilillah, and spiritual steadfastness (istiqāmah) aligned with Surah Ar-Rum verse 60. Sosiologically, the site serves a dual purpose as a social cohesion binder and a driver for the local creative economy. We conclude that to safeguard the site's economic sustainability and spiritual values from the risks of desacralization, an inclusive governance restructuring is required, driven by digital promotion and local community empowerment.